A comparison study of the existing requirements ambiguity detection framework - Seh Wali, Siti Syara Aiman; Nordin, Azlin; Salleh, Norsaremah (IEEE Explore, 2025)
Software requirements ambiguity is a common issue that can lead to miscommunication, project delays, and increased costs. This paper provides an extensive evaluation of existing frameworks designed to detect ambiguity in requirements engineering. Through comparison and analysis, the study assesses the methods, advantages, and disadvantages of various frameworks. The results highlight the effectiveness of the existing approaches and identify areas in which more investigation and enhancement are needed. The significance of identifying ambiguity to enhance the quality of software requirements is emphasized by this investigation. It also offers important insights for further advancement in this field. With an emphasis on improving the quality of requirements, the study's contributions are intended to help practitioners and researchers improve the efficiency and reliability of requirements engineering techniques.